Ohlin on the Great Depression: The popular message in the daily press - Benny Carlson; Lars Jonung (Stockholm School of Economics, The Economic Research Institute (EFI), 2001)
This paper traces the development of Bertil Ohlin's views on issues such as the causes of the depression of the 1930's, policies against the depression, the use of fiscal and monetary policies, and tariffs and public works to stabilize the business cycle. We examine about 80 of his articles on the depression of the 1930's, published in Stockholms-Tidningen, a Stockholm daily, between 1926 and 1935. This is a small sample of Ohlin's total output of more than 2 300 contributions to the daily press - a number that makes him the most prolific economic journalist of all Swedish professors of economics in the 20th century. Our basic result is that Ohlin was an eager but cautious commentator on current affairs. Initially, he was quite optimistic, underestimating the depth of the depression. Later, as the depression worsened, he proposed bolder measures such as increased public works and public investments as well as an expansionary monetary policy to fight unemployment. By 1932, Ohlin had adopted a multiplier approach. He was strongly opposed to cuts in nominal wages and public expenditures during the depression. Summarizing his views on the depression in 1934, Ohlin concluded that it was not the result of any inherent weakness of capitalism. Turning to the perennial debate on the originality of the Stockholm School: Do Ohlin's daily articles show him as a pioneer or as an orthodox in macroeconomic thinking in the 1930's? We conclude that support for either interpretation can be heralded. However, Ohlin appears more radical in his academic writings than in his newspaper articles - a view supported by Ohlin himself in his memoirs.
Keywords: B20; B31; E24; E60; N14; 330; Bertil Ohlin; the great depression; the Stockholm School; fiscal and monetary policy; keynesian macroeconomics